2008
DOI: 10.1111/j.1749-4877.2008.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Alien species of mammals and their impact on natural ecosystems in the biosphere reserves of Russia

Abstract: The paper analyses the results of a survey of 37 Russian biosphere reserves using questionnaires concerning the presence of alien species of mammals, their pathways of penetration, and their impacts on protected ecosystems. The penetration of alien mammals into terrestrial ecosystems of Russia is extensive, both in places with maximum human environmental impact (inhabited areas and agricultural lands) and in biosphere reserves with minimal human impact. There are 62 mammal species registered as alien in Russia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…1. Eurasian part of the muskrat (Ondatra zibethicus) range and its dynamics within the Soviet Union Neronov et al, 2008). The territory settled by the muskrat: (1) selves are smaller.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Eurasian part of the muskrat (Ondatra zibethicus) range and its dynamics within the Soviet Union Neronov et al, 2008). The territory settled by the muskrat: (1) selves are smaller.…”
Section: Resultsmentioning
confidence: 99%
“…In studying alien species, it is important to know what regions and ecosystems are influenced by them, as well as who the invaders are and what the degree of their diversity is. Our previous stud ies (Bobrov et al, 2008b;Khlyap et al, 2008Neronov et al, 2008;Bobrov et al, 2011) have allowed solving these problems in terms of mammals for such a wide and heterogeneous territory as Russia. The goal of this article is to differentiate the territory of Russia according to diversity of alien mammal species and identify the regions which are under the greatest influ ence of invaders.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the introduced raccoon dog may pose a threat to populations of ground nesting birds and amphibians, especially during their respective breeding seasons [5], [6], [7], [8]. However, the results of Naaber [5], Rätsepp [16] and this study suggest that the quantity of amphibians and birds in raccoon dog diet in Estonia depends on the season and that outside their respective breeding seasons, consumption of birds and amphibians generally remains low (though amphibians were a fairly important food source in autumn: FO = 13.9%).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most successful invasive carnivores in Europe is the raccoon dog ( Nyctereutes procyonoides ) [3], which is suspected of causing damage to native fauna through its feeding habits. Although insects, plants and small mammals are the main food objects for raccoon dogs in Europe [4], the species is an opportunistic feeder and is considered a potential threat to ground nesting birds and amphibians [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Szaro (2008) examines some general issues and challenges facing nature conservation, and some lessons learnt by the International Union of Forest Research Organization. Implications for the management of protected areas arising because of our changing climate are discussed by MacKinnon (2008) who uses several examples from China, while Neronov et al (2008) present their work on invasive mammals and the impact on ecosystems from studies of biosphere reserves in Russia. Pov (2008) reviews the literature and properties of the newly-described deuterobiosphere and its associated ecosystem complexes.…”
Section: In This Issuementioning
confidence: 99%